Swoistość prawnokarnej ochrony praw pracownika a jedność funkcji prawa karnego i prawa pracy - Kowalewska-Borys, Ewa (Kwartalnik Prawa Publicznego, 2016)
The following considerations are an attempt to answer the question of how, on the basis of various branches of law, i.e. substantive penal law and labor law, the constructs of legal solutions in their specific form affect the unity of these two laws. The author begins the article by presenting the classic division into public law, which penal law forms part of, and private law, which labor law forms part of. She also indicates its essence and the most important characteristics, and then discusses the relationship between the provisions of the penal code and labor code on criminal liability for breach or threat to basic law, i.e. employee rights related to employment relationship or social security, on one hand from the perspective of the unity of penal law and labor law, and on the other from the perspective of the specificity of the penal law structure. The analysis of penal provisions governing criminal liability for infringement of labor rights leads to the conclusion that the unity of penal and labor law, from the standpoint of the specificity of penal-law protection of employee rights, demonstrates that the unity of both branches does not preclude the creation and good functioning of specific constructs of legal solutions, combining the elements of both areas. The instruments of private labor rights protection are too weak and ineffective to ensure the full protection of the employee, being undoubtedly weaker on the part of the employment relationship. The legislator, thus, has rightly regulated the legislation related to penal law.